The PENGARUH TEKANAN KETAATAN, KOMPLEKSITAS TUGAS DAN KEAHLIAN AUDIT TERHADAP AUDIT JUDGEMENT - BAMBANG SAMBODO; Ivone Fitriani (Jurnal Ilmiah Wahana Bhakti Praja, 2020)
The research method used in this study is a quantitative descriptive research method with the research population taken by the author is the Auditor at BPK RI representative office on Kepulauan Riau province with a total of 37 people and all populations are used as research samples. The data analysis technique used is the Multiple Linear Regression Test for testing the Hypothesis. Partially Compliance Pressure (X1), Task Complex (X2) and Audit Expertise (X3) have a significant effect on Audit Judgment (Y). Simultaneously Compliance Pressure, Task Complexity and Audit Expertise Significantly Influences Audit Judgment at BPK RI representative office on Kepulauan Riau province.